(untitled) (Homoeopathy for All, 2023)
Cardiovascular disease is the most frequent diagnosis in elderly people and it is the leading cause of death in both men and women older than 65 years of age. The high morbidity and mortality from cardiovascular disease warrant aggressive approaches to prevention and treatment that have been shown to be effective in older patients. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of coronary heart disease (heart attack) for elder peoples.